RESERVASI DAN BILLING POST OF TRANSACTION RESTAURANT GRAHA KARDOPA BINJAI SECARA ONLINE - Aula, Nurhasanah; Fauzi, Achmad; Pardede, A M H; Maulita, Yani; Buaton, Relita (STMIK Kaputama, 2020)
Hotel Graha Kardopa is a Hotel located in Binjai, North Sumatra. System Information about reservation and billing in this Hotel still use manual system, where the way is still be regarded very slowly. To facilitate the processing of billing in need of Information System Reservation and Billing Post Of Transaction Restaurant Graha Kardopa Binjai. Based on the problems that have been in carefully by the author, the authors designed the Information Systems Reservation And Billing Post Of Transaction Restaurant Graha Kardopa Binjai. The result of this research is to facilitate the processing of Reservation and Billing Restaurant Hotel Graha Kardopa Binjai. The purpose of this Final Project is to make an Information System Reservation and Billing Post Of Transaction Restaurant Graha Kardopa Binjai, by using PHP and MySql-based programming Web that can help the process of restaurant reservation processing to be effective and efficient.